Coexistence of Chronic Lymphocytic Leukemia and Myeloproliferative Neoplasm - Patrycja Zielinska; Miroslaw Markiewicz; Monika Dzierzak-Mietla; Anna Koclega; Grzegorz Helbig; Slawomira Kyrcz-Krzemien (Case Reports in Oncological Medicine)
Chronic lymphocytic leukemia (CLL) is the most common adult leukemia in the Western world. Host immune surveillance caused mainly by the disease itself is speculated to be responsible for high incidence of secondary neoplasms. However, the simultaneous occurrence of CLL and myeloproliferative disorder in the same patient is extremely rare. In the present report, a case of an 81-year-old man who was diagnosed with chronic lymphocytic leukemia and concomitant essential thrombocythemia is presented. We describe the morphologic, immunophenotypic, cytogenetic, and molecular findings in this patient. We also review the current literature.